Review—Multifunctional Separators: A Promising Approach for Improving the Durability and Performance of Li-Ion Batteries. Issue 3 (1st January 2019) - Banerjee, Anjan; Ziv, Baruch; Shilina, Yuliya; Ziegelbauer, Joseph M.; Liu, Hanshuo; Harris, Kristopher J.; Botton, Gianluigi; Goward, Gillian R.; Luski, Shalom; Aurbach, Doron; Halalay, Ion C.
Abstract : Electrified vehicles require Li-ion batteries (LIBs) with 10-year useful life. We review herein our progress since 2016 in the understanding of dissolved Mn species and LIB performance degradation by multifunctional materials. Multifunctional separators (MFSs), can trap Mn cations, scavenge acid species, and/or dispense alkali metal ions, with significant battery performance benefits: increased capacity retention during electrochemical cycling and improved rate performance. Cells with LiMn2 O4 (LMO), LiNi0.6 Mn0.2 Co0.2 O2 (NCM622), or LiNi0.5 Mn1.5 O4 (LNMO) positive electrodes, graphite negative electrodes, and LiPF6 /mixed organic carbonate solutions were investigated. XRD, ICP-OES, XANES, HR-SEM, FIB-SEM, and MAS-NMR on harvested cell components complemented and aided the interpretation of electrochemical test results. While in LIBs with positive electrodes affected by Mn dissolution cell performance improvements can be enabled by delaying and then impeding the deposition of transition metal (TM) ions deposition at negative electrodes through their trapping by MFS, acid scavenging separators provide a more general approach that can enable performance benefits in cells with non-spinel positive electrode materials such as NCM622, as well as with 5 V class positive electrode materials such as LNMO. We illustrate our discussion with both previously published and new data. We conclude with a discussion of remaining challenges, new opportunities, and recommendations for future work.